Deciphering the Coagulation Factors in Pulmonary Embolism Incident-Based Thorax Enhanced Chest CT in COVID-19 Patient - Wan Betty Pratiwi; Noni Novisari Soeroso; Setia Putra Tarigan; Muntasir Abdullah; Rosita Juwita Sembiring; Azizah Ghanie Icksan; Netty Delvrita Lubis; Putri Chairani Eyanoer (Jurnal Respirasi, 2023)
Introduction: Pulmonary embolism is associated with coagulopathy in COVID-19. It is one of the causes of death in COVID-19 cases and is often underdiagnosed in Indonesia because computed tomography-pulmonary angiography (CTPA) is not used as the gold standard. T Methods: This study used a prospective analytical design with a cross-sectional approach. The study participants were 45 COVID-19 patients admitted to Santa Elisabeth Hospital, Medan, from January to March 2021.  Patients were identified with moderate to severe degrees of COVID-19 and elevated D-dimer and subsequently instructed to undergo a thorax CT scan with IV contrast. The data was analyzed using dependent t-test statistical analysis. The p-value < 0.05 was noted as significant. Results: Moderate to severe coagulation factor values in COVID-19 patients with mean + SD PT, APTT, D-dimer, fibrinogen, and platelets were 14.11; 30.65; 1172.14; 423.56 and 215.822, respectively. In this study, 22 (48.9%) patients experienced a pulmonary embolism, while the other 23 (51.1%) did not. No significant correlation was found between all coagulation factors and embolism (p > 0.05). The mean + SD well score for pulmonary embolism was 0.23 + 0.57. Conclusion: Pulmonary embolism was detected in 22 patients (48.49%) with moderate to severe COVID-19 who developed hypercoagulation as indicated by the thorax CT scan with IV contrast. This case was quite common. In resource-constrained situations, a thorax CT scan with IV contrast may replace CTPA in diagnosing/detecting the presence of pulmonary embolism.